Avaliação do módulo de elasticidade de argamassas utilizando diferentes métodos de ensaio com vistas a uma caracterização quanto à fadiga - Noberto, Camila Carvalho (2022)
In Brazil, the existence of problems related to fatigue in external coating mortars is common, especially in sunny façades. Variations arising from temperature and humidity can result in the appearance of tensile stress, which, repeatedly, can induce the appearance of cracks in the mortar coating system, due to the phenomenon of fatigue. The phenomenon depends on material properties such as the coefficient of thermal expansion, the modulus of elasticity and the resistance to fatigue itself. However, this defect is not commonly investigated, creating gaps in its evaluation, due to the lack of tests and analysis methods that are important means of assessing the possible effects of fatigue and predict and avoid them with adequate selection of materials and material design. Then, the objective of the research is to evaluate the modulus of elasticity of coating mortars, considering different test methods, with regards to characterizing fatigue, including the preliminary assembly of a test for this purpose. Elastic modulus and fatigue tests, and an example of simplified estimation of the fatigue life of external coating mortars was proposed. The study included two different mortars, one conventional (A) and one industrialized (B), for five ages (3, 7, 14, 30 and 56 days). Tests of the following types were carried out to determine the modulus of elasticity: static test, classically used for concrete; quasi-static test, with sinusoidal loading at different levels of loading amplitude (10%, 20% and 30% of static resistance); and ultrasonic pulse velocity test. Furthermore, the ultrasound test, in some materials, was carried out in an intercalated manner between the other tests, with the aim of evaluating damage effects, even at loading amplitudes considered small. The results showed that the complex modulus of coating mortars is influenced by the frequency and amplitude of loading, which should be considered in fatigue analysis in the field, where loading frequency is much lower than in lab tests. Furthermore: the modulus of elasticity increases with increasing age; there is evidence of damage in the modulus tests at earlier ages (up to 30 days), while, for more advanced ages, the damage resulting from the complex module test is low, which justifies considering it as non- destructive. Furthermore, a uniaxial fatigue test was proposed as part of this research. It is expected that the existence of a protocol for predicting defects resulting from fatigue, as this work sought to contribute, can help to reduce their occurrence acting early in design phases.